How Does AI Enable Virtual Reality Rehabilitation? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Virtual reality (VR) is no longer a concept confined to science fiction. It has emerged as a powerful tool in healthcare, particularly in the field of rehabi...
Keywords: AI in Rehabilitation Medicine; Enable; Virtual; Reality; Artificial Intelligence; Healthcare